The sun does shine eaudiobook How i found life and freedom on death row (oprah's book club summer 2018 selection). - Hinton, Anthony Ray (Macmillan Audio, 2018)
Oprah's Book Club Summer 2018 Selection A powerful, revealing story of hope, love, justice, and the power of reading by a man who spent thirty years on death row for a crime he didn't commit. "An amazing and heartwarming story, it restores our faith in the inherent goodness of humanity." —Archbishop Desmond Tutu In 1985, Anthony Ray Hinton was arrested and charged with two counts of capital murder in Alabama. Stunned, confused, and only twenty–nine years old, Hinton knew that it was a case of mistaken identity and believed that the truth would prove his innocence and ultimately set him free. But with no money and a different system of justice for a poor black man in the South, Hinton was sentenced to death by electrocution. He spent his first three years on Death Row at Holman State Prison in agonizing silence—full of despair and anger toward all those who had sent an innocent man to his death. But as Hinton realized and accepted his fate, he resolved not only to survive, but find a way to live on Death Row. For the next twenty–seven years he was a beacon—transforming not only his own spirit, but those of his fellow inmates, fifty–four of whom were executed mere feet from his cell. With the help of civil rights attorney and bestselling author of Just Mercy, Bryan Stevenson, Hinton won his release in 2015. With a foreword by Stevenson, The Sun Does Shine is an extraordinary testament to the power of hope sustained through the darkest times. Destined to be a classic memoir of wrongful imprisonment and freedom won, Hinton's memoir tells his dramatic thirty–year journey and shows how you can take away a man's freedom, but you can't take away his imagination, humor, or joy. This program includes a forward written and read by Bryan Stevenson. Praise for The Sun Does Shine audiobook: "The incredible details of Hinton's trial and eventual release are narrated in an honest, easy style by Kevin R. Free...He captures the Southern rhythms of Hinton's speech with a natural cadence that brings us closer to his pain." — AudioFile Magazine "Kevin R. Free performs this work with flashes of anger cast over a deep humility, and captures the sense of humor that Hinton was, incredibly, able to hold on to during his long years in solitary confinement...This is a story that enrages and inspires." — New York Times